Manhaj Penulisan Fiqh 'abd Al-Karim Zaydan Dalam Kitab Al-Mufassal Fi Ahkam Al-Mar’ah - Mukhlis Bakri; Ibnor Azli Bin Ibrahim; Muhammad Adib Bin Samsudin (Penerbit Kemala Indonesia, 2023)
This paper aims to investigate the manhaj writing of Fiqh on the book of al-Mufassal Fi Ahkam al-Mar’ah Wa al-Bayt al-Muslim Fi al-Sharicah al-Islamiyyah that it’s written by Syeikh CAbd al-Karim Zaydan.This book is seen as having a special feature compared to other fiqh books because in addition to the universal aspects of the content , it also has a very thorough writing methodology. The research methodology used in this article is in a qualitative form and uses literature review methods, journals and interviews. The results of this study found that there were 14 manhaj of fiqh writing used by Sheikh Zaydan in writing al-Mufassal, namely; referring to original fiqh sources, expressing consent, presenting clauses, expressing opinions of friends, relying on the opinions of famous scholars, expressing diligent fiqh views, presenting differences in the opinions of scholars without tarjih, expressing moderate fiqh views, suggesting equations and differences in fiqh between men with women, reaching maqasid al-sharicah, paying attention to the ease of fiqh, expressing current understanding of fiqh, presenting emergency as a concession, and presenting the wisdom of a law.